The Effectiveness of Computer-Assisted Instruction on Students’ Cognitive Skill to Know Geometric Shapes - Nurul Khotimah; Nur Ika Sari Rakhmawati; Rachma Hasibuan (Faculty of Education Universitas Negeri Malang, 2020)
Abstract: Cognitive skill, the important aspect in early childhood development, consists of three skills such as learning and problem solving, symbolic thinking and logical thinking. The activities in recognizing geometric shapes in children aged 4-5 years are by mentioning geometric shapes, showing geometric shapes, and geometric grouping shapes. The result of observation shows children are difficult to distinguish between square and rectangular shapes when asked. Thus, educational media to overcome these problems as well as to meet the industrial revolution 4.0 challenge is so needed. This study aims to determine the effect of CAI (Computer Assisted Instruction) on children aged 4-5 years in recognizing geometric shapes. This is quantitative descriptive research using a quasi-experimental design with a non-equivalent control group design. The population used were 75 children aged 4-5 years. Data were collected using observation and documentation. The assessment indicators used are to mention geometric shapes, show geometric shapes, connect 2- and 3-dimensional geometry shapes (surrounding objects), and group surrounding objects. Computer-Assisted Instruction (CAI) in recognizing geometric shapes was used 3 times. The average score before treatment was 10.77, while after treatment was12.66. Through the Mann-U Whitney test, the hypothesis was sig equals 0,000 is less than alpha (0.05) meaning that Ho was rejected and Ha was accepted. Therefore, it can be concluded that CAI (Computer Assisted Instruction) is an effective media to recognize geometric shapes in children aged 4-5 years.